PERAN KEPALA DESA DALAM PENGELOLAAN TEMPAT PELELANGAN IKAN MILIK DESA DI DESA PENASO KECAMATAN PINGGIR KABUPATEN BENGKALIS TAHUN 2015 - Rianto "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the village of Kuala Penaso Uptown District of Bengkalis district. In this study, the village chief who acts as coordinator, should be able to resolve the various problems during the activities undertaken for the development program that became the main tasks of the village government, of course, can not be running as well as you want, without any cooperation or coordination between the authorities and development it will not be accomplished with baiktanpa their participation and support of the entire apparatus of the village. This study using interview techniques.In doing construction in the village of Kuala Penaso village chief role in development activities is certainly need for a coordination between the Head of the Village, the Village, BPD, LKMD, LPM and Community Leaders that the planned development was right on target and the public can feel the benefits of development.Results of research transactions are carried out based on interviews with several informants found that the role of the village chief in the management of the fish auction belonged to the village has been done but still less effective where, according to the informant from the community (fishermen) socialization of TPI in the village of Kuala Penaso rarely done by the head of the village so that people TPI reluctant to occupy in the village of Kuala Penaso.Keywords : Policy, Management, Fish Auction, Kuala Penaso vilage